A Perspective on the Uses and Misues of Standardized Achievement Tests - Airasian, Peter W.; National Council on Measurement in Education, East Lansing, MI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The nature and common uses of standardized achievement tests are described and placed in context in order to evaluate claims and criticisms that are commonly made. Tests are described as samples of behavior and hence subject to sampling errors. Much of the debate is dominated by emotion and prejudices. There is very little empirical evidence about the effects of tests as a part of the complex educational situation. Test results are misused if they are treated as exact and permanent indices of achievement; if they are used as the sole basis for making important decisions; if the constructs they measure are misinterpreted; or if they are interpreted as caused only by the content of the test. Within the classroom, test scores may legitimately be used as supplements to other information available to the teacher. Outside the classroom, where other information may be less available, the use of tests for accountability decisions is more questionable; but the demands for student and teacher accountability are strongly supported and there may be no other, more credible, information available. The school and classroom are evaluative environments and evaluations will continue to be made. (Author/CTM)
Availability: National Council on Measurement in Education, USPS 823120, 1230 17th Street, N.W., Washington, DC 20036 ($1.50).
NCME Measurement in Education, v10 n3 Fall 1979.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Achievement Tests; Decision Making; Educational Objectives; Educational Policy; Educational Testing; Elementary Secondary Education; Measurement Techniques; Scores; Standardized Tests; Test Interpretation; Test Reliability; Test Results; Test Validity; Testing Problems; Opinion Papers; Collected Works, Serials